Оптимальный расход основного конденсата через встроенные пароохладители в подогревателях низкого давления турбоустановок мощностью 300 МВт - Братута, Эдуард Георгиевич; Ганжа, Антон Николаевич; Марченко, Наталья Андреевна (Одесский национальный политехнический университет, 2008)
The procedure and algorithms of optimizing water flow rate through built-in attemperators in low-pressure heaters of 300 MW turbo-installations are developed. The efficiency function in the optimization problem is the minimum of specific consumption price. With regard for constraints, the optimal water flow range at prescribed values of device’s economic characteristic is determined.
Optimal quantity of full-flow condensate through built-in attemperator in low-pressure heaters of turbo-installation power 300 MW
Keywords: пароохладители; турбоустановки; регенеративный подогрев воды; подогреватели низкого давления; энергоблоки; электрическая энергия